Perancangan Dan Implementası Iklan Vıdeo IG TV Pada Outfıt Batam Store - Diny Anggriani Adnas; Mudrikah Nur Fauzi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
One of the businesses that is now getting more and more enthusiasts is the distribution business. Distro is a fashion business that sells local and international brand products. The higher the need for fashion, the more motivated business people to make an innovation that is even more creative. Through secial media, business people can promote their products easily and are able to reach a wider audience. This study aims to design and implement IGTV video advertisements on distribution products. The research design of IGTV video advertisements uses applied research methods. İn implementing this IGTV video ad, the author uses data collection methods, namely by observation and interviews. This IGTV advertising video has the aim of being a product promotion media that will be implemented on the Outfit Batam Store’s Instagram account.